2011
DOI: 10.1177/0165025411398181
|View full text |Cite
|
Sign up to set email alerts
|

The dual impact of gender and the influence of timing of parenthood on men’s and women’s career development: Longitudinal findings

Abstract: This study investigated the impact of gender, the gender-related self-concept (agency and communion), and the timing of parenthood on objective career success of 1,015 highly educated professionals. Hypotheses derived from a dual-impact model of gender and career-related processes were tested in a 5-wave longitudinal study over a time span of 10 years starting with participants’ career entry. In line with our hypotheses we found that the communal component of the gender self-concept had an impact on parenthood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 24 publications
3
67
0
2
Order By: Relevance
“…These women may realise that change may not occur unless they make the change. This pattern supports previous studies that show women to be more likely to make work adjustments than men (Abele & Spurk, 2011;Becker & Moen, 1999;Kuhhirt, 2012;Sanchez & Thomson, 1997;Schober & Scott, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These women may realise that change may not occur unless they make the change. This pattern supports previous studies that show women to be more likely to make work adjustments than men (Abele & Spurk, 2011;Becker & Moen, 1999;Kuhhirt, 2012;Sanchez & Thomson, 1997;Schober & Scott, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…The birth of the first child seems to remain 'a critical juncture in the development of a gender gap in time spent on paid work and household labour' (Schober, 2013, p. 83). Women often decrease their employment hours when they become mothers (Abele & Spurk, 2011;Kuhhirt, 2012) although the difference in work hours between mothers and childless women is not as large in Sweden (Misra et al, 2011).…”
Section: Parenthood and Work Adjustmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was showed that A values were linked with variables that were related with life satisfaction (Çivitçi and Çivitçi, 2009;Kong, Ding and Zhao, 2014), such as, self-esteem and self-efficacy beliefs (Abele, 2003). On the other hand, studies show that A traits predicted success, achievement, assertive actions, political behaviors, and competence in an individual's occupational career (Abele, 2003;Abele and Spurk, 2011). A values instigate behavior which is success-oriented and leads to actual to success (Abele, 2014: 4).…”
Section: The Roles Of Aandc Values On Political Deviance and Job Relatementioning
confidence: 97%
“…Consider the following. Many women who want to excel as much as their male counterparts are limited by childcare obligations (see Abele & Spurk, 2011 ) . As described in The Washington Post (de Daniel, 2010 ) , a 2005 Virginia Tech report found that the number of "voluntary" departures of female faculty members was disproportionate to that of males; women accounted for one-fi fth of the faculty but two-fi fths of departures.…”
Section: Individual Sources Of Dilemmasmentioning
confidence: 99%